Pelatihan Pengolahan Sekam Mentah Menjadi Media Tanam Melalui Proses Fermentasi pada Mahasiswa Pendidikan Biologi - Harisanti, Baiq Muli; Hajiriah, Titi Laily; Fatmawati, Any (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
The objectives of this service activity are: (1) to introduce and train the abilities of Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education students in planting media in the form of raw husks which will be processed into fermentated husks; (2) Forbidding to students that smoked husks are a good planting medium for ornamental plants. Service activities carried out within 1 day. The stages of this service activity are: (1) Introduction; (2) Initial Fermentation Process Practice Activities; (3) Continuation Activities (observations for 3 weeks). The 1 day activity is used to process raw husks that have just been taken from the rice mill, then fermented using EM4 as a bioactivator (observations after 3 weeks). Based on the results of the activity evaluation, it can be interpreted that the objectives of this service activity have been achieved as expected. This achievement can be seen from the ability of students to process raw husks into cooked husks which are ready to be used as a planting medium for ornamental plants.